2008
DOI: 10.1021/jp711329f
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Diphenylbutadiene and Donor−Acceptor Functionalized Derivatives:  Exploring the Competition between Conjugation Paths in Branched π-Systems

Abstract: 2,3-Diphenylbutadiene and its donor-acceptor functionalized derivatives represent branched pi systems consisting of three overlapping linearly conjugated units, namely a 1,3-butadiene and two phenylethene subsystems. The evaluation of pi conjugation using a scheme based on the natural bond orbital analysis shows that the details of the structure of these compounds is governed by electron delocalization. The potential energy surface of 2,3-diphenylbutadiene shows two minima, each one representing a distinct com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…These observations prompted us to explore the evolution of π-conjugation in PA, PDA, and PTA. For that matter, we studied the response of selected physical observables to the length of the backbone, and related these observations to the evolution of the delocalization energy along the π-conjugated chain using a new scheme based on the natural bond orbital (NBO) analysis. The NBO analysis was shown to be a useful tool for the investigation of π-conjugation in earlier work. , …”
Section: Introductionmentioning
confidence: 99%
“…These observations prompted us to explore the evolution of π-conjugation in PA, PDA, and PTA. For that matter, we studied the response of selected physical observables to the length of the backbone, and related these observations to the evolution of the delocalization energy along the π-conjugated chain using a new scheme based on the natural bond orbital (NBO) analysis. The NBO analysis was shown to be a useful tool for the investigation of π-conjugation in earlier work. , …”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42] The objective of this paper is to provide a systematic investigation of the title compounds in order to devise rules connecting the structural features ͑in particular, chain length, donor/acceptor nature, and strength͒ to the resulting values for BLA, polarizability and hyperpolarizability. This is expected to provide useful structure/ property relationship, which can then be exploited to design systems with particular characteristics across one or multiple properties.…”
Section: Introductionmentioning
confidence: 99%
“…From a NBO population analysis Limacher and Lu ¨thi revealed a ground state effect on the p-electrons of compound DA2. 39 Butler-Ricks et al showed that in a donor-acceptor substituted diphenylethene the s-electron system may be dominant in charge transport. 16 In this respect it is of interest to compare the behavior of DA1 with that of data for molecules containing an N,N-dimethylaniline donor and a cyanophenyl acceptor separated by a bridge consisting of a single sp 3 carbon atom like compound 1C.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The calculated conformations are in agreement with geometries calculated by Limacher and Lu ¨thi. 39 The lowest energy structure of DA2 is thus different from the s-trans structure that was initially assumed, 32 and this might have a bearing on the understanding of the behaviour of the compound. In the butterfly-like s-gauche geometry DA2 possesses a compact structure, whereas in the s-trans conformation the geometry is extended.…”
Section: Molecular Structuresmentioning
confidence: 95%
See 1 more Smart Citation